Programmatic and Legal Preparedness of India on Early Childhood Development - Prasanth Subrahmanian; Shilpa Singh; Ashutosh Kothari (Preventive Medicine: Research & Reviews)
Early childhood development (ECD) is the period of rapid and critical development that occurs from conception upto 6 to 8 years of age. During this time, children experience significant growth and changes in all areas of development, including physical, cognitive, linguistic and socio - emotional. A variety of factors can influence ECD, including genetics, environment and health. This presents a unique opportunity to invest in ECD and build a foundation for a prosperous and equitable future for the country. This review looked at the programmatic and legal preparedness of India in taking forward the agenda of ECD. A review of the laws and programs was undertaken to discern this objective. Besides desk review, interviews were conducted with programme officers handling child health at the central and state levels. Based on the direction for action given by the national health and other policies and several statutes, the central government has launched various programmes and schemes under various ministries within the overarching framework provided by the Constitution of India. There are 5 policies, 15 statutes/acts/laws and nearly 40 government schemes and programmes relating to children in India. The activities are majorly coordinated through Ministries of Woman and Child Development, Health and Family Welfare, Ministry of Education, Drinking Water and Sanitation and Tribal Affairs. Despite these efforts, there is still a significant gap between the demand and supply for ECD services.